Efficacy of high-power and short-duration ablation in patients with atrial fibrillation: a prospective randomized controlled trial. Issue 10 (18th August 2020) - Shin, Dong Geum; Ahn, Jinhee; Han, Sang-Jin; Lim, Hong Euy
Abstract: Aims: The formation of radiofrequency lesions depends on the power and duration of ablation, and the contact force (CF). Although high power (HP) creates continuous and transmural lesions, most centres still use 25–30 W for 30–40 s for safety reasons. We evaluated the clinical efficacy and safety of a HP and short-duration (HPSD) strategy for atrial fibrillation (AF) ablation. Methods and results: One hundred and fifty patients [58.2 ± 10.0 years, 48% with paroxysmal AF (PAF)] scheduled for index AF ablation using a CF-sensing catheter were randomly assigned to three groups [30 W, 40 W, and 50 W at ablation sites of anterior, roof, and inferior segments of pulmonary vein (PV) antra and roof line between each upper PV]. In 25–30 W for ≤20 s was applied at posterior wall ablation site in all subjects. Compared with the 30 W and 40 W groups, procedure ( P  < 0.001) and ablation times ( P  < 0.001) were shorter and ablation number for PV isolation ( P  < 0.001) was smaller in the 50 W group. There were no significant differences in the CF and ablation index (AI) among the three groups. There were no significant differences in the procedure-related complication rates. During the 12-month follow-up, AF recurred in 24 (16%) patients with no significant difference among the groups ( P  = 0.769). In the multivariate analysis, non-PAF [hazard ratio (HR) 2.836, P  = 0.045] and AI (HR 0.983, P  = 0.001) were independent risk factors for AF recurrence. Conclusion: Radiofrequency ablation with HPSD is a safe and effective strategy with reduced ablation number and shortened procedure time compared to conventional ablation.